Rola kierownika w kształtowaniu świadomości ekologicznej pracowników przedsiębiorstwa - Zaremba-Warnke, Sabina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article contains the analysis of importance of environmental activity for a contemporary enterprise and shows that the main condition of environmental changes in a firm is high level of employees' environmental awareness. The article also contains the list of instruments which are used to build up employees' environmental awareness and also shows that managers play a leading role in that process. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 167-175